A rare case report of haemolytic uremic syndrome in post caesarean section - Gaikwad, Priyanka; Deshmukh, Jyotsna; Godbole, Viraj; Pandey, Shailja (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Haemolytic uremic syndrome (HUS) is a clinical syndrome characterised by progressive kidney failure associated with microangiopathic haemolytic anemia and thrombocytopenia. Women may be genetically predisposed to develop HUS which gets aggravated by pregnancy. We presented a case of 25 year old G2p1l1 with h/o 9 months amenorrhoea was admitted in active labour, underwent emergency caesarean section for non-progression of labour. Postoperatively patient had decreased urine output with unexplained thrombocytopenia with deranged renal function tests and increased serum LDH with normal coagulation profile and no any evidence of foci of infection for which HUS was suspected. Patient was treated with hemodialysis, plasmapheresis and other supportive medical treatment.